INCLUSION AND TERRITORIAL EQUITY IN THE URBAN PLANNING AGENDA OF MEDELLÍN – COLOMBIA - Isabel Duque Franco (Bollettino della Società Geografica Italiana)
During the last decade, Medellin (Colombia) has been recognized al international level for its urban transformation, having gone from being the most unsafe city to the most innovative city in the world. This article discusses this transformation from the incorporation of territorial inclusion and equity in the agenda of urban planning of the city. The aim of the paper is to analyze some of the urban policies developed in Medellin between 2004 and 2011 from the perspective of inclusion and territorial equity. In this sense, urban policies are examined from the narratives that inspire them and some of the practices and ways of realization.